Grade book options - Selecting personal view options - (:unkn) unknown (University of Wisconsin Board of Regents, 2003)
Grade book personal view options, allow you to have some preset columns turned off or on in the grade book area. Such as, Username, ID, email, grade colours, show weighted grade and show percent. You can also decide to display user details every number of grade items so that as you scroll to the right you can match a column with the students name.
Keywords: Desire2Learn; Gradebook